(untitled) (Belügyi Szemle, 2024)
Aim: Criteria for the evaluation by the Constitutional Court of decisions on the execution of sentences. Methodology: Descriptive, documentary and content analysis. Findings: According to the Section 27 (1) of the Act on the Constitutional Court, the decision on the merits, i.e. the decision on the substance of the charge and the decision on criminal responsibility, or the decision on the guilt and the acquittal, can be the subject of a constitutional complaint. The final decisions – the order not to proceed to trial and the order terminating the proceedings – cannot be considered as decisions on the merits within the meaning of the Constitutional Court Act. However, these decisions can be examined in the context of a constitutional complaint, because they correspond to the Section 27 (1) of the Constitutional Court Act, the other decision ending the court proceedings. Value: So far, no academic article has been published that analyses which decisions of the penitentiary judges can be challenged by a constitutional complaint following the latest amendments to Act CCXL of 2013 (Act XCVII of 2023).